Coronary Angiography Characteristics as Predictor of Successful Chronic Total Occlusion Recanalization - Oktaviono, Yudi Her; Rizal, Ardian; Al-Farabi, Makhyan Jibril; Maghfirah, Irma; Rachmi, Dita Aulia (International Journal of Angiology, 2020)
Although remarkable progress in percutaneous coronary intervention (PCI) has been achieved over the last decade, the success rate of chronic total occlusion (CTO) recanalization varies greatly. Coronary angiography characteristics may affect the success rate of CTO recanalization. This study sought to establish a scoring model to predict successful CTO recanalization based on coronary angiography characteristics. We analyze 287 angiography data from patients who underwent elective PCI. Angiography characteristics being measured were lesion location, blunt stump, calcification, ostial lesion, bridging collateral, bending, side branch, tortuosity, previous stent attempt, and lesion length of >20 mm. Data were analyzed using SPSS 25.0. Multivariate analysis shows that side branch lesion (p = 0.000), proximal vessels tortuosity (p = 0.015), calcified lesion (p = 0.000), lesion length of >20 mm (p = 0.000), and blunt stump (p = 0.000) can predict the successful PCI in the CTO. ROC curve analysis of the score ability to predict successful PCI in the CTO showed area under curve of 0.89 (confidence interval 95%), the cutoff point of ≤2 with a sensitivity of 93.33%, and specificity of 88.23%. We concluded that the five angiography characteristics that strongly associate with successful PCI in the CTO are calcified lesion, blunt stump, lesion length >20 mm, proximal vessel tortuosity, and side branch lesion. This score may help cardiologists to predict the success probability of PCI in the CTO.
Keywords: angiography; angioplasty; CTO; recanalization; score